WILAYAH STUDI DAN KAJIAN KEISLAMAN: STUDI DAN PENELITIAN TENTANG ISLAM - Saerozi, Saerozi (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2011)
Studies and researches on Islam are faced with a hope of how to give answer for the gap accure between the ideality of the teachings of the religion on one side and the reality of life and human understanding and rational interpretation which are more and move omproved of all things. A demand to ?make? the teachings of religion ?objective? becomes more and more strong. There for, an effort to formulate the relevance between what is essential to a religion and what becomes the dynamics of thoughts of its ummah is a must as well as a challenge. Through studies af and research on Islam, it is hoped that they can bridges the relevance of the teaching of the religion to the needs of modernity of the era.